Optimizing Morning Exercise Management: Evaluating the Impact of Fitness Programs at GBLA Bandung on Public Health Enhancement - Sudiantini, Dian; candra, juli (PT. BERBAGI TEKNOLOGI SEMESTA, 2025)
The management of morning exercise programs plays a crucial role in promoting public health. This study focuses on evaluating the effectiveness of fitness program management at GBLA Bandung, particularly morning exercise sessions, as a means to enhance public health outcomes. Utilizing a mixed-method approach, both quantitative and qualitative data were gathered through surveys, interviews, and observations of program participants. The analysis revealed significant improvements in physical health indicators, including cardiovascular fitness and body mass index, among regular participants. Additionally, the study identified key factors in program management that contributed to participant retention and engagement, such as the quality of instruction, accessibility, and community involvement. These findings underscore the importance of structured management in maximizing the public health benefits of fitness programs. The study also offers recommendations for optimizing program delivery to achieve broader health impacts in similar urban settings. This research contributes to the growing body of literature on sports management and public health, offering practical insights for policymakers and program managers aiming to foster healthier communities through well-managed exercise initiatives.